Expression Toll-like receptors in the oral mucosa of patients with recurrent aphthous stomatitis - Diah Savitri Ernawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Toll-like receptors (TLRs) have recently emerged as key receptors of the innate immune system. They recognize specific pathogenassociated molecular patterns initiating a host defence response. The oral mucosa epithelium encounters potential pathogens like bacteria and viruses in inspired air, and the discovery of TLRs on epithelial cells suggest that the epithelium has a role in the mucosal immune system. The aim of this study was to discover Recurrent Apthous Stomatitis (RAS) using etiopathogenetic molecular approach by observing the TLRs. Immunohistochemistry using monoclonal antibodies anti-TLR-2, TLR-3, TLR-4, TLR-5, TLR-7 and TLR-9 were used in this study. These antibodies are specific toward TLR on the surface of epithelial cells membrane and macrophages in patients with major and minor RAS. TLR was expressed on the surface of epithelial cells membrane of oral mucosa and macrophages in both major and minor RAS patients. TLRs was not expressed specifically in non-RAS patients. The results above showed indication, that functional TLRs expression by epithelial cells in oral mucosa had remarkable implication on natural immune response and disease pathogenesis. The expression of TLR was found in the oral mucous membrane on epithelial cells surface and macrophages patients with RAS.